Sustainability and Climate Adaptation: Using Google Earth to Engage Stakeholders - Stocker, Laura; Burke, Gary; Kennedy, Deborah; Wood, David (Nature Publishing group, 2012)
This action-research project aimed to test a participatory mapping methodology using Google Earth to develop shared understandings among participants about sustainability and climate change. The process focused on improving knowledge uptake and enabling dialogue among participants in order to develop adaptation strategies for Rottnest Island, off the Western Australian coast. Project results indicate increased levels of knowledge and commitment to active involvement in sustainability and climate change issues. Common threads came together in a coherent set of recommendations that will contribute to ongoing climate change and sustainability planning by the Rottnest Island Authority. Major conclusions drawn include: the usefulness of Google Earth for participatory planning for climate adaptation and sustainability; the methodology enables social, economic, ecological and cultural layers to be considered without any having primacy; care must be taken to ensure knowledge and power differential are managed effectively; and, the methodology brought together stakeholders and scientists to co-produce knowledge and decisions.